HARAPAN PASANGAN USIA SUBUR (PUS) DALAM MENGIKUTI PROGRAM KELUARGA BERENCANA (KB) DI DESA MUARA UWAI KECAMATAN BANGKINANG - Maemunaty, Titi Maemunaty; Irja, Desti Irja (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The population issue is one of the issues that affect the prosperity of society. One of the factors causing the occurrence of the problems of this population is the population explosion. Therefore, it should be an attempt to control population growth appropriately. One of them is through the Family Planning Program (FPP). The number of Fertile-Age Couple (FAC) who follow the Family Planning Program (FPP) in Muara Uwai village, Bangkinang district, which in reality, their parents say âmany children a lot of sustenance,â Fertile-Age Couple (FAC) want to pursue their careers and a door prize given each year. The aim of this study was to determine the level of expectations of Fertile-Age Couple (FAC) in the Family Planning Program (FPP).The design of this study is descriptive study, the population of this study is 50 people. In this case the sample is 30 people and 20 people for trial. This study used Simple Random Sampling. The sampling technique is applied when a member of a population is considered to be homogeneous. Data collection techniques used are library study and field study consisting of dissemination of questionnaires, observations, and interviews. The data analysis technique used was by testing the questionnaire. And data processing techniques performed manually done from the results of the questionnaire and then tabulated in the form of frequency distribution and then analyzed.The results of data analysis showed that the expectation of Fertile-Age Couple (FAC) in following Family Planning Program (FPP) in Muara Uwai village Bangkinang district is high. Thus, Fertile-Age Couple (FAC) have a high expectation in following Family Planning Program (FPP).Keywords: Expectation, Fertile-Age Couple, and Family Planning Program